ESTUDIO PARA MEJORAR LA SEGURIDAD DE LA RED DE LA EMPRESA PARIS.NET DEL CANTÓN VINCES - Benites Hidalgo, Jorge Luis (2018)
At present in several companies it is necessary to incorporate and implement information technologies, in order to improve the organization, automation, information generated and optimize resources, however this reality will not be feasible, without having a good security policy. Paris.Net is an ISP company (Internet Service Provider), located in Quito and Machinaza streets of Vinces canton, Los Ríos province, its commercial activity is to provide internet services to the community. Protecting a system often requires deactivating services, blocking and limiting software features that can easily be the gateway to a system, in this way a number of weaknesses are being compressed to a large extent. It seeks to identify the different vulnerabilities left by the former managers in charge of configuring and managing networks, weakening the possible attacks carried out by viruses and hackers, as well as correcting errors in communications. " The development of this case study, describes the sub-line of research of the career that are the processes of data transmission and telecommunications, the methodology used is the quantitative method, because this method is the most used for this research which allows open, closed and multiple choice questions using the information and data variables. That is, it tries to analyze and delimit the association, the generalization and the object of the results obtained when studying a population. The technique that was used is the survey.